The effect of Discussion Method and Cognitive Style on Students’ Reading Comprehension Achievements at One Indonesian University - YANTI ISMIYATI; TAHRUN TAHRUN; INDAWAN SYAHRI; MAKMUR MAKMUR (Edukasi, 2018)
The purpose of this study is to investigate the effect of discussion method and cognitive style on students’ reading comprehension achievement. This research was an experimental study with factorial design. The total number of sample of this study was 50 students selected with claster sampling technique. The data of this study consisted of the scores on reading comprehension either through pre-test and post-test for experimental and control classes and the scores of cognitive style of the pre-test and post-test. Based on data analysis with two way Annova, the value of F- calculated is =14.40 > than the value of F table =1.64. So, the hypothesis one “There is significant effect of discussion method on students’ reading comprehension achievements” is accepted. Two-way Annova analysis also found that the value of F- calculated on facto b (independent and dependent cognitive style) is = 0.158 < than the value of F- table = 1.64. So, the hypothesis which says “There is any significant effect of cognitive style on students’ reading comprehension achievements” is rejected (Ha is rejected and Ho is accepted). Then two-way Annova analysis found that the value of F- calculated is =3.803 > than the value of F- table =1.64. So, the hypothesis three which says” There is any significant effect on students’ reading comprehension achievements” is accepted (Ha is accepted and Ho is rejected). Based on findings, it can be concluded that this research has mixed results.